STRENGTHENING PEACE EDUCATION POST POSO CONFLICT TO SUPPORT NATIONAL SECURITY - Arifuddin Uksan; Achmed Sukendro; Yulian Azhari (Bajang Institute, 2024)
The communal conflict that occurred in Poso from 1998 to 2004 was a dark and gloomy episode in the history of the Indonesian nation and a series of acts of terror that were triggered by radical understanding. This research aims to analyze conflict resolution as an effort to strengthen positive peace after social conflict in Poso. The research method used is descriptive qualitative with data collection through interviews, observation and documentation studies. The results of the research findings on the Poso conflict were riots between native residents and immigrants which spread to ethnic, religious, racial and inter-group conflicts. Factors that cause conflict are rooted in economic problems between native people and immigrants, transfer of agricultural land, social inequality, as well as political problems, namely struggles for structural and political positions between native people and immigrants who happen to represent the same religious community, as well as socio-cultural problems, namely changes in composition. the population makes the native population feel marginalized. As a conclusion of the research, the Ethnic, Religious, Racial and Intergroup conflict that occurred in Poso Regency was a complex conflict in terms of the root of the problem, which was then triggered by provocateurs who wanted riots to occur in order to gain profits from the conflict that occurred. Efforts to strengthen positive peace education after the Poso conflict are very important as the right solution to support national security.